Comparing Two Waist-to-Height Ratio Measurements with Cardiometabolic Risk Factors among Youth with Diabetes - Liu, Lenna L.; Kahn, Henry S.; Pettitt, David J.; Fino, Nora F.; Morgan, Tim; Maahs, David M.; Crimmins, Nancy A.; Lamichhane, Archana P.; Liese, Angela D.; D’Agostino Jr., Ralph B.; Bell, Ronny A. (International Journal of Child Health and Nutrition, 2016)
Background: Waist circumference (WC) is commonly measured by either the World Health Organization (WHO) or National Health and Nutrition Examination Survey (NHANES) protocol. Objective: Compare the associations of WHO vs. NHANES WC-to-height ratio (WHtR) protocols with cardiometabolic risk factors (CMRFs) in a sample of youth with diabetes. Methods: For youth (10–19 years old with type 1 [N=3082] or type 2 [N=533] diabetes) in the SEARCH for Diabetes in Youth Study, measurements were obtained of WC (by two protocols), weight, height, fasting lipids (total cholesterol, triglycerides, HDL cholesterol, Non-HDL cholesterol) and blood pressures. Associations of CMRFs with WHO and NHANES WHtR were modeled stratified by body mass index (BMI) percentiles for age/sex: lower BMI (<85th BMI percentile; N=2071) vs. higher BMI (≥85th percentile; N=1594). Results: Among lower-BMI participants, both NHANES and WHO WHtR were associated (p<0.005) with all CMRFs except blood pressure. Among higher-BMI participants, both NHANES and WHO WHtR were associated (p<0.05) with all CMRFs. WHO WHtR was more strongly associated (p<0.05) than NHANES WHtR with triglycerides, non-HDL cholesterol, and systolic blood pressure in lower-BMI participants. Among high-BMI participants, WHO WHtR was more strongly associated (p<0.05) than NHANES WHtR with triglycerides and systolic blood pressure. Conclusion: Among youth with diabetes, WHtR calculated from either WC protocol captures cardiometabolic risk. The WHO WC protocol may be preferable to NHANES WC.